Progenitor/Stem Cells Give Rise to Liver Cancer Due to Aberrant TGF-β and IL-6 Signaling - Tang, Yi; Kitisin, Krit; Jogunoori, Wilma; Li, Cuiling; Deng, Chu-Xia; Mueller, Susette C.; Ressom, Habtom W.; Rashid, Asif; He, Aiwu Ruth; Mendelson, Jonathan S.; Jessup, John M.; Shetty, Kirti; et al. (Proceedings of the National Academy of Sciences - PNAS, 2008)
Cancer stem cells (CSCs) are critical for the initiation, propagation, and treatment resistance of multiple cancers. Yet functional interactions between specific signaling pathways in solid organ "cancer stem cells," such as those of the liver, remain elusive. We report that in regenerating human liver, two to four cells per 30,000-50,000 cells express stem cell proteins Stat3, Oct4, and Nanog, along with the prodifferentiation proteins TGF-β-receptor type II (TBRII) and embryonic liver fodrin (ELF). Examination of human hepatocellular cancer (HCC) reveals cells that label with stem cell markers that have unexpectedly lost TBRII and ELF. $elf^{+/-}$ mice spontaneously develop HCC; expression analysis of these tumors highlighted the marked activation of the genes involved in the IL-6 signaling pathway, including IL-6 and Stat3, suggesting that HCC could arise from an IL-6-driven transformed stem cell with inactivated TGF-β signaling. Similarly, suppression of IL-6 signaling, through the generation of mouse knockouts involving a positive regulator of IL-6, Inter-alpha-trypsin inhibitor-heavy chain-4 (ITIH4), resulted in reduction in HCC in $elf^{+/-}$ mice. This study reveals an unexpected functional link between IL-6, a major stem cell signaling pathway, and the TGF-β signaling pathway in the modulation of mammalian HCC, a lethal cancer of the foregut. These experiments suggest an important therapeutic role for targeting IL-6 in HCCs lacking a functional TGF-β pathway.